The Level of Acquisition of Geographical Concepts Among Students of the Fourth and Fifth Grades "Field Study in Basic Education Schools in Lattakia Governorate" (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
The aim of the research is to identify the level of acquisition of the basic fourth and fifth graders of geographical concepts in the unit "My Environment" of the fourth grade social studies book, and to reveal the differences between them according to the variable of the place of residence.To achieve this goal, the descriptive approach was used, then the test of acquiring geographical concepts was used, and its validity and reliability were confirmed, and it was distributed to a sample of (200) male and female learners of the fourth and fifth graders in the city of Lattakia and its countryside.The results showed that the level of acquiring geographical concepts for the fourth and fifth graders was low, and the level of the fourth graders' acquisition of geographic concepts was higher than the level of acquisition of the fifth grade learners, and there was no difference in the level of acquiring geographical concepts for the fourth and fifth graders in the countryside and the city.In light of the research results, he suggested the necessity of focusing on geographical concepts and their acquisition methods for the fourth and fifth graders, and using modern educational models and strategies that help in their acquisition and development.